R2D2 spherical TPC: first energy resolution results. (4th March 2021) - Bouet, R.; Busto, J.; Cecchini, V.; Cerna, C.; Dastgheibi-Fard, A.; Druillole, F.; Jollet, C.; Hellmuth, P.; Katsioulas, I.; Knights, P.; Giomataris, I.; Gros, M.; et al.
Abstract: Spherical time projection chambers (TPC), also known as spherical proportional counters, are employed in the search for rare phenomena, such as light Dark Matter candidates. The spherical TPC exhibits a number of essential features, making it a promising candidate for the search of neutrinoless double beta decay (ββ0ν). A tonne-scale spherical TPC experiment could cover a region of parameter space relevant for the inverted mass hierarchy with a few years of data taking. In this direction, the major R&D goal of the R2D2 effort is the demonstration of the required energy resolution. First results from an argon-filled prototype detector are reported, demonstrating an energy resolution of 1.1% FWHM for 5.3 MeV α tracks in the 0.2 to 1.1 bar pressure range. This is a major milestone in terms of energy resolution, paving the way for further studies with xenon gas, and the possible use of this technology for ββ0ν searches.